3D conservation planning: Including aquifer protection in freshwater plans refines priorities without much additional effort. Issue 7 (14th June 2019) - Linke, Simon; Turak, Eren; Asmyhr, Maria Gulbrandsen; Hose, Grant
Abstract: Groundwater has very rarely been included in modern systematic conservation planning methods that identify key areas for protection of aquatic organisms. Three conservation plans were developed for aquatic ecosystems in the Hunter Valley, NSW, Australia using the planning software Marxan: one model for rivers and wetlands and two that consider groundwater ecosystems. The first of these groundwater inclusive models included aquifers in the initial planning process; the second retrofitted groundwater onto an existing conservation plan. The results demonstrate that, if groundwater protection was included at the planning stage, the overall land that was needed only increased marginally. When included, groundwater protection led to an emphasis on groundwater recharge zones. A posteriori inclusion of GW protections, however, yielded a 30% increase in surface area needing protection. We conclude that groundwater can be included in conservation planning but it is much more efficient to do so at the beginning of the planning process. The next step is to refine the planning methods by including data on groundwater‐dependent organisms, either by genetic means or novel statistical techniques, and hence using a direct biotic signal instead of environmental surrogates.